Optimal design of multiple damped-outrigger system incorporating buckling-restrained braces. (1st September 2019) - Lin, Pao-Chun; Takeuchi, Toru; Matsui, Ryota
Abstract: The outrigger system is an effective solution in mitigating seismic responses of core-tube-type tall buildings by mobilizing the axial stiffness of the perimeter columns. The concept of damped-outrigger has been proposed which introduces dampers in the outrigger system to dissipate seismic energy. This study investigates the seismic behavior of a damped-outrigger system incorporating buckling-restrained brace (BRB-outrigger). The outrigger effect combined with the energy dissipation mechanism of the buckling-restrained brace (BRB) effectively reduce the seismic response of the building. This study proposes the methods to evaluate the inelastic seismic response of structures with multiple damped-outriggers based on a spectral analysis (SA) procedure. For the structure with BRB-outriggers, the optimal outrigger elevations, and the relationships between the axial stiffness of the BRB, the axial stiffness of the perimeter column, and the flexural rigidity of the core structure in order to minimize the seismic response are the primary research objectives of this study. Analytical models with building heights of 64 m, 128 m, 256 m, and 384 m are used to perform the SA and the nonlinear response history analysis. This study concludes with a design recommendation for preliminary design purposes.